Nitrate Pathways, Processes, and Timing in an Agricultural Karst System: Development and Application of a Numerical Model. Issue 3 (14th March 2019) - Husic, A.; Fox, J.; Adams, E.; Ford, W.; Agouridis, C.; Currens, J.; Backus, J.
Abstract: Nitrogen (N) contamination within agricultural‐karst landscapes and aquifers is widely reported; however, the complex hydrological pathways of karst make N fate difficult to ascertain. We developed a hydrologic and N numerical model for agricultural‐karst, including simulation of soil, epikarst, phreatic, and quick flow pathways as well as biochemical processes such as nitrification, mineralization, and denitrification. We tested the model on four years of nitrate (NO3 − ) data collected from a phreatic conduit and an overlying surface channel in the Cane Run watershed, Kentucky, USA. Model results indicate that slow to moderate flow pathways (phreatic and epikarst) dominate the N load and account for nearly 90% of downstream NO3 − delivery. Further, quick flow pathways dilute NO3 − concentrations relative to background aquifer levels. Net denitrification distributed across soil, epikarst, and phreatic water removes approximately 36% of the N inputs to the system at rates comparable to nonkarst systems. Evidence is provided by numerical modeling that NO3 − accumulation via evapotranspiration in the soil followed by leaching through the epikarst acts as a control on spring NO3 − concentration and loading. Compared to a fluvial‐dominated immature karst system, mature‐karst systems behave as natural detention basins for NO3 −, temporarily delaying NO3 − delivery to downstream waters and maintaining elevated NO3 − concentrations for days to weeks after hydrologic activity ends. This study shows the efficacy of numerical modeling to elucidate complex pathways, processes, and timing of N in karst systems. Key Points: Slow (epikarst and phreatic) flows account for nearly 90% of nitrate loading in an agricultural‐karst system Nitrate accumulation and subsequent leaching dominate pathway processes Agricultural‐karst systems act as detention basins of nitrate and, during flood recession, drain storm‐derived nitrate more gradually compared to poorly karstified systems